Analisis Kelayakan Bisnis Terhadap Aspek Pasar pada Usaha Laundrybox di Tanjungpinang : Penelitian - Afriyadi, Afriyadi; Amelia, Amelia; Zalma, Delvina Azalia; Sulanjari, Halimah; Kheirani, Meilita Putri; Anggraini, Rezi; Sellina, Sellina; Putri, Tri Yuni; Amalia, Tria; Lestari, Vita Ayu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the feasibility of LaundryBox Branch 60 in Tanjungpinang based on market aspects using a marketing mix approach that includes product, price, place, and promotion. The research method used is descriptive qualitative with data collection through observation, direct interviews with employees, and literature studies from secondary sources. The results of the analysis show that LaundryBox provides a variety of laundry services that suit the lifestyle of urban communities with high mobility, such as kilo laundry, single item laundry, and express services with varying completion times. Competitive pricing that is comparable to the quality of service, as well as a strategic location in the Tugu Pahlawan area, provide easy access for customers from various segments such as students, office workers, and young families. Digital promotion strategies through social media and membership programs effectively increase loyalty and expand market share. In addition, free pick-up and delivery services expand market reach and provide added value. Overall, LaundryBox is considered feasible from a market perspective and has strong growth prospects with good competitiveness in the Tanjungpinang area. Recommendations are given to strengthen digital promotion and service development for business sustainability.